A Guide to professional doctorates in business & management - Anderson, Lisa (Lecturer in management education); Gold, Jeffrey; Stewart, Jim, 1952-; Thorpe, Richard, active 2015 (Los Angeles : Sage, 2015)
Are you undertaking (or thinking of doing) a Doctor of Business Administration (DBA) or other professional doctorate (PD) in business and management? Or perhaps you're supervising and delivering one of these programmes? This is your complete - and practical - guide to succeeding on this course. A Guide to Professional Doctorates in Business and Management has been written by a team of experts with experience of the challenges faced in both studying for and supervising professional doctorates in business and management. Inside they address the key issues faced, in particular how these courses differ from a traditional PhD, and the different skills and approach needed for success. Chapters explore the nature and importance of PDs as leading change in the professional world of practice, and ...
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Industrial management -- Study and teaching (Higher); Industrial management -- Research; Industrial management -- Research; Industrial management -- Study and teaching (Higher)